(untitled) (Docentes 2.0 Journal, 2017)
The constructive mental activity that the student puts into play this set of elements, develops around the content is configured, from this perspective, as a fundamental key to learning, and the quality of such constructive mental activity, therefore, is arranged as a fundamental key to the quality of learning: neither every activity that the student performs when learning entails constructive mental activity, nor all constructive mental activity is equally desirable or optimal for quality learning.